2020
DOI: 10.3390/atmos11091004
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Simulated PM2.5 Concentrations over Northeast Asia to Different Secondary Organic Aerosol Modules during the KORUS-AQ Campaign

Abstract: A numerical sensitivity study on secondary organic aerosol formation has been carried out by employing the WRF-Chem (Weather Research and Forecasting model coupled with Chemistry). Two secondary organic aerosol formation modules, the Modal Aerosol Dynamics model for Europe/Volatility Basis Set (MADE/VBS) and the Modal Aerosol Dynamics model for Europe/Secondary Organic Aerosol Model (MADE/SORGAM) were employed in the WRF-Chem model, and surface PM2.5 (particulate matter less than 2.5 μm in size) mass concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…This underestimation occurs due to uncertainty in estimating VOC volatility, which is related to the complex SOA generation mechanisms used for SOA simulation. Hence, the results of secondary OC formation simulations differ greatly according to the treatment of VOC volatility [31,33]. The underlying drivers of inter-model biases thus originate from the complexity of the SOA formation process, and the use of three different SOA formation modules in our study, as indicated in Table 1, might have directly caused the inter-model variability in OC distribution simulations (Figure 5).…”
Section: Concentrations Of Pm 25 and Its Chemical Componentsmentioning
confidence: 86%
“…This underestimation occurs due to uncertainty in estimating VOC volatility, which is related to the complex SOA generation mechanisms used for SOA simulation. Hence, the results of secondary OC formation simulations differ greatly according to the treatment of VOC volatility [31,33]. The underlying drivers of inter-model biases thus originate from the complexity of the SOA formation process, and the use of three different SOA formation modules in our study, as indicated in Table 1, might have directly caused the inter-model variability in OC distribution simulations (Figure 5).…”
Section: Concentrations Of Pm 25 and Its Chemical Componentsmentioning
confidence: 86%
“…Detailed model evaluations for several models (including our simulations) during KORUS-AQ are found in Park et al ( 2021) [40]. The results of the comparisons of the WRF-Chem with DC-8 aircraft measurements during the KORUS-AQ campaign period for some case studies can be also found elsewhere [47,48].…”
Section: Park Et Al (2021)mentioning
confidence: 95%
“…The Wintertime Investigation of Transport, Emission, and Reactivity observations (WINTER, https://data.eol.ucar.edu/dataset/483.025, last access: 14 June 2022) are mainly carried out over the sea and land of the eastern US (Green et al., 2019). The International Cooperative Air Quality Field Study in Korea (KORUS‐AQ, https://espo.nasa.gov/korus-aq/content/KORUS-AQ, last access: 14 June 2022) is concentrated around South Korea (Lee et al., 2020).…”
Section: Methodsmentioning
confidence: 99%